2015
DOI: 10.7453/gahmj.2015.034.suppl
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Studies of Biofield Therapies: Summary, Methodological Challenges, and Recommendations

Abstract: Biofield therapies are noninvasive therapies in which the practitioner explicitly works with a client's biofield (interacting fields of energy and information that surround living systems) to stimulate healing responses in patients. While the practice of biofield therapies has existed in Eastern and Western cultures for thousands of years, empirical research on the effectiveness of biofield therapies is still relatively nascent. In this article, we provide a summary of the state of the evidence for biofield th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
80
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 70 publications
(111 reference statements)
0
80
1
2
Order By: Relevance
“…In recent years, Biofield Energy Treatment (The Trivedi Effect ® ) has been reported worldwide as an alternative treatment method which has been known for its significant impact on various cancerous cells [12]. According to many scientific studies, Biofield Energy Healing has been reported to have significant outcomes that may prove to be a more cost effective alternative to other approaches [13]. Complementary and Alternative Medicines (CAM) are now rising as preferred method of treatment, among which Biofield Therapy (or Healing Modalities) is one approach that has been reported to have several benefits to enhance physical, mental and emotional human wellness.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Biofield Energy Treatment (The Trivedi Effect ® ) has been reported worldwide as an alternative treatment method which has been known for its significant impact on various cancerous cells [12]. According to many scientific studies, Biofield Energy Healing has been reported to have significant outcomes that may prove to be a more cost effective alternative to other approaches [13]. Complementary and Alternative Medicines (CAM) are now rising as preferred method of treatment, among which Biofield Therapy (or Healing Modalities) is one approach that has been reported to have several benefits to enhance physical, mental and emotional human wellness.…”
Section: Introductionmentioning
confidence: 99%
“…According to many scientific studies, Biofield Energy Healing has been reported to have significant outcomes that may prove to be a more cost effective alternative to other approaches [18]. Complementary and Alternative Medicines (CAM) are now rising as preferred models of treatment, among which Biofield Therapy (or Healing Modalities) is one approach that has been reported to have several benefits to enhance physical, mental and emotional human wellness.…”
Section: Introductionmentioning
confidence: 99%
“…Human Biofield Energy has subtle energy that has the capacity to work in an effective manner [20]. Reports show that CAM therapies have been practiced worldwide with reports of clinical benefits in different health disease profiles [21].…”
Section: Introductionmentioning
confidence: 99%